Estudio de la eficacia en la administración de levotiroxina en ayunas en comparación con la noche a realizarse en el Hospital del IESS de Loja y Clínica Mogrovejo. - Yupangui Ortega, Jonathan Bladimir (2017)
The determination of TSH is the most sensitive parameter for the diagnosis of hypothyroidism. This phenomenon occurs before the concentrations of thyroid hormones that begging to descent into the blood. The objective of the research is to determine the efficacy in the administration of levothyroxine in fasting compared with the night in patients with hypothyroidism treated in external consultation at “Manuel Ygnacio Monteros” hospital and “Clinica Mogrovejo” clinic. In the methodology a comparative study was elaborated, experimental, quantitative cross-sectional, the population was constituted by 300 patients who attended to the IESS hospital and a private practice, the sample corresponds to the universe in study to which an informed consent sheet was delivered. The survey was used as a collection tool, where general patient data TSH levels onset values and side effects were recorded. The results concluded that 75% of patients who received levothyroxine at night decreased the administered doses, a value that exceeds the result observed in the morning. Significant differenced were obtained depending on the percentage of patients who: they continued with the onset dose, increased the dose and showed adverse effects. Keywords: Thyroid stimulating hormone (TSH) - Hypothyroidism - Levothyroxine